Пошаговое объяснение:
1. подстановки:
║ х - у = 4,
║ х² - 2у = 11,
из 1 ур-ия:
х = у + 4,
подставим во 2 ур-ие:
(у+4)² - 2у = 11,
у² + 8у + 16 - 2у = 11,
у² + 6у + 5 = 0,
Д = 6² - 4*1*5 = 36 + 20 = 16,
у1 = (-6 + 4) / 2*1 = -2/2 = -1,
у2 = (-6 - 4) / 2*1 = -10/2 = -5,
х1 = -1 + 4 = 3,
х2 = -5 + 4 = -1,
2. сложения:
║ х - у = 4, (х -2)
║ х² - 2у = 11,
║ -2х + 2у = -8,
║ х² - 2у = 11,
-2х + 2у + х² - 2у = -8 + 11,
-2х + х² = 3,
х² - 2х - 3 = 0,
Д = (-2)² - 4*1*(-3) = 4 + 12 = 16,
х1 = (2 + 4) / 2*1 = 6/2 = 3,
х2 = (2 - 4) / 2*1 = -2/2 = -1,
из 1 ур-ия:
у = х - 4,
у1 = 3 - 4 = -1,
у2 = -1 - 4 = -5,
3. графически:
решение на фото
⇅ ⇅ ⇅
ответ: (3; -1), (-1; -5)
Пошаговое объяснение:
1. подстановки:
║ х - у = 4,
║ х² - 2у = 11,
из 1 ур-ия:
х = у + 4,
подставим во 2 ур-ие:
(у+4)² - 2у = 11,
у² + 8у + 16 - 2у = 11,
у² + 6у + 5 = 0,
Д = 6² - 4*1*5 = 36 + 20 = 16,
у1 = (-6 + 4) / 2*1 = -2/2 = -1,
у2 = (-6 - 4) / 2*1 = -10/2 = -5,
х1 = -1 + 4 = 3,
х2 = -5 + 4 = -1,
2. сложения:
║ х - у = 4, (х -2)
║ х² - 2у = 11,
║ -2х + 2у = -8,
║ х² - 2у = 11,
-2х + 2у + х² - 2у = -8 + 11,
-2х + х² = 3,
х² - 2х - 3 = 0,
Д = (-2)² - 4*1*(-3) = 4 + 12 = 16,
х1 = (2 + 4) / 2*1 = 6/2 = 3,
х2 = (2 - 4) / 2*1 = -2/2 = -1,
из 1 ур-ия:
у = х - 4,
у1 = 3 - 4 = -1,
у2 = -1 - 4 = -5,
3. графически:
решение на фото
⇅ ⇅ ⇅
ответ: (3; -1), (-1; -5)
10/24-21/54=5/12-7/18=(5*3-7*2)/36=(15-14)/36=1/36
30/54+22/30=5/9+11/15=(5*5+11*3)/45=(25+33)/45=58/45=1_13/45
28/40-10/75=7/10-2/15=(7*3-2*2)/30=(21-4)/30=17/30
12/27+14/21=4/9+2/3=(4+2*3)/9=(4+6)/9=10/9=1_1/9
14/24-15/40=7/12-3/8=(7*2-3*3)/24=(14-9)/24=5/24
12/18-5/60=2/3-1/12=(2*4-1)/12=(8-1)/12=7/12
4/24+3/36=1/6+1/12=(2+1)/12=3/12=14